Incorporation of STED technique into single-molecule spectroscopy to break the concentration limit of diffusing molecules in single-molecule detection. Issue 69 (13th August 2018) - Kim, Namdoo; Kwon, Jiwoong; Lim, Youngbin; Kang, Jooyoun; Bae, Sohyeon; Kim, Seong Keun
Abstract : Incorporation of STED into ALEX-FRET increases the concentration limit of single-molecule detection by 100-fold to 5 nM. Abstract : By incorporating STED (stimulated emission depletion) nanoscopy into single-molecule spectroscopy, we demonstrate that the concentration limit imposed by optical diffraction can be overcome in diffusion-based single-molecule measurement. We showed that single-molecule detection is feasible at a concentration of 5 nM, which is 100-times higher than the limit of conventional single-molecule measurements.